Implementing radar reflector‐guided localization of nonpalpable breast lesions: Feasibility, challenges, outcomes, and lessons learned. Issue 7 (3rd April 2021) - Misbach, Laura Semine; Karimova, Evguenia Jane; Cronin, Claire; James, Ted; Brook, Alexander; Dialani, Vandana
Abstract: Reflector‐guided localization uses a nonradioactive radar implant for wire‐free presurgical breast lesion localization. A single‐institution retrospective evaluation found lower rates of positive margins and of close margins for reflector‐guided localizations compared with wire localizations, resulting in a statistically significant decrease in the re‐excision rates ( p = 0.015). The two approaches did not show statistically significant difference in localization time and OR time. Technical challenges included particulars inherent in reflector placement, while patient factors included special considerations for reflector placement in the postsurgical breast. Despite novel challenges, we found reflector‐guided localization to be accurate and efficient.